2017
DOI: 10.1186/s12885-017-3322-5
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative cholesterol level as a new independent predictive factor of survival in patients with metastatic renal cell carcinoma treated with cyto-reductive nephrectomy

Abstract: BackgroundThe obesity and lipid metabolism were previously proposed to be related with the clinical outcomes of metastatic renal cell carcinoma (mRCC). We tried to investigate the relationship between preoperative cholesterol level (PCL) and survival outcomes in patients with mRCC.MethodsWe analysed the data of 244 patients initially treated with cyto-reductive nephrectomy after being diagnosed with mRCC. Patients were stratified into two groups according to the PCL cut-off level of 170 mg/dL. The postoperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 22 publications
0
15
0
3
Order By: Relevance
“…The basic clinical characteristics of the enrolled studies (12)(13)(14)(15)(21)(22)(23)(24)(25) are provided in Table 1. For the study design, the nine included studies were retrospective cohorts and published from 2014 to 2019.…”
Section: Study Characteristics and Quality Evaluationmentioning
confidence: 99%
See 4 more Smart Citations
“…The basic clinical characteristics of the enrolled studies (12)(13)(14)(15)(21)(22)(23)(24)(25) are provided in Table 1. For the study design, the nine included studies were retrospective cohorts and published from 2014 to 2019.…”
Section: Study Characteristics and Quality Evaluationmentioning
confidence: 99%
“…Few studies included only locally or metastatic RCC patients (14,23), but most studies reported the inclusion of generalized RCC patients (12,13,15,21,22,24,25). Overall survival (OS) was reported in five studies (12)(13)(14)(15)23), cancer-specific survival (CSS) was assessed in six studies (14,(21)(22)(23)(24)(25), and progression-free survival (PFS) was evaluated in four studies (12,14,15,25). Finally, HRs and corresponding 95% CIs were sufficiently provided by all included studies.…”
Section: Study Characteristics and Quality Evaluationmentioning
confidence: 99%
See 3 more Smart Citations